2023
DOI: 10.1111/ffe.14079
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐based fatigue life prediction: A review

Abstract: The main objective of this review paper is twofold: Recall the most captivating areas of research in predicting the fatigue life of metals with the application of thermal methodology, particularly for the stress‐controlled fatigue tests. The explicit lifetime models reviewed have been developed by scholars over the past two decades owing to the advancements in infrared thermal imaging technology. Introduce, discuss, and conclude a broad range of alternative theoretical frameworks in thermodynamics. Some inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 132 publications
(238 reference statements)
0
4
0
Order By: Relevance
“…However, even with a lot of work completed, a thorough review of infrared thermography techniques is still needed. Despite the review by Teng et al [5] and Mohammad et al [38] having advanced the understanding of the thermodynamic framework, criteria for determining fatigue limit based on threshold or bi-linear approaches have not yet been discussed. Furthermore, the discussion and further perspectives on the fatigue limit determination based on the non-linear response relationship have not been well addressed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, even with a lot of work completed, a thorough review of infrared thermography techniques is still needed. Despite the review by Teng et al [5] and Mohammad et al [38] having advanced the understanding of the thermodynamic framework, criteria for determining fatigue limit based on threshold or bi-linear approaches have not yet been discussed. Furthermore, the discussion and further perspectives on the fatigue limit determination based on the non-linear response relationship have not been well addressed.…”
Section: Figurementioning
confidence: 99%
“…Finally, mechanical structures may suffer greatly from unexpected fatigue-fractured components, which can result in large financial losses and, in some cases, fatalities [4]. Statistics data show that fatigue failure is responsible for over 90% of metallic structural failure accidents [5]. Therefore, to quickly and accurately estimate the fatigue performance of mechanical structural components, the scientific and industrial sectors must implement a fair, efficient, and scientific fatigue evaluation of mechanical components.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, after the presentation of the concept of fracture fatigue entropy (FFE) by Naderi et al, 19 a great interest in studying the fatigue phenomenon with thermodynamic bases was established. [20][21][22][23] The main base of the entropy works mentioned above is that the rate of dissipation of energy ΔW per cycle during a fatigue process reaches a constant value after a certain time, which remains constant for each cycle during the rest of the process until the failure of the material. [24][25][26][27][28] Under this assumption, Morrow 24 developed a pioneer work in which he established a relationship between fatigue life and the cyclic dissipation of energy.…”
Section: Introductionmentioning
confidence: 99%
“…Vito et al [7] investigated the effect of a weaker heat of the wrought form of Haynes 282 nickel superalloy on creep rupture and maximum allowable working stress, and showed the importance of minimizing heat to heat variability of properties on high temperature creep strength. Teng [8] reviewed various thermo-based fatigue life prediction methods, and both theoretical background and experimental techniques are given. Michael et al [9] used over 100 creep tests of a cast austenitic stainless steel and Larson-Miller model to predict long-term lifetimes as functions of temperature and stress, and results showed that the Larson-Miller approach is more robust when treating rupture-time datasets with wide experimental scatter.…”
Section: Introductionmentioning
confidence: 99%